Centromere 17 copy number gain reflects chromosomal instability in breast cancer - Lee, Kyoungyul (Sci Rep, 2019)
Chromosomal instability (CIN) is known to be associated with prognosis and treatment response in breast cancer. This study was conducted to determine whether copy number gain of centromere 17 (CEP17) reflects CIN, and to evaluate the prognostic and predictive value of CIN in breast cancer. CIN status was determined by summing copy number gains of four centromeric probes (CEP1, CEP8, CEP11, and CEP16) based on fluorescence in situ hybridization and CIN scores were calculated using next generation sequencing data. High CIN was associated with adverse clinicopatholgical parameters of breast cancer. Among them, positive HER2 status, high Ki-67 index and CEP17 copy number gain were found to be independent predictors of high CIN. High CIN was associated with poor clinical outcome of the patients in the whole group, as well as in luminal/HER2-negative and HER2-positive subtypes. CEP17 copy number was significantly higher in the high-CIN-score group than in the low-CIN-score group. A positive linear correlation between the mean CEP17 copy number and the CIN score was found. In conclusion, CEP17 copy number was confirmed as a useful predictor for CIN in breast cancer, and high CIN was revealed as an indicator of poor prognosis in breast cancer.